The Voice of Academics on Omnibus Law on YouTube: Undermining Public Transparency - Nurul Hasfi; Ahsani Taqwim Aminuddin (Ikatan Sarjana Komunikasi Indonesia, 2022)
Agenda-building is concerned with negotiating interests in social systems and forces structured and carried out by a group of people. This study explores the agenda-building of the academics to intervene in the Job Creation Act (UUCK) policies that are delivered through YouTube. UUCK is an omnibus law, regulations made based on the compilation of rules with different substances and levels. UUCK in Indonesia was passed on October 5, 2020, with the main aim of simplifying regulations to improve the investment climate in Indonesia. However, the law has been opposed by many groups of people, starting from workers, students, academics, NGOs, and environmental activists, because the law is considered to be not pro-people. This study analysed dialogue texts about UUCK using agenda-building theory in 12 dialogue videos with a total duration of 25 hours and 40 minutes on YouTube uploaded in 2020. This research shows that YouTube facilitates public voices represented by academics amid positive narratives about UUCK that are spread in the mass media and the internet. The study has found four significant narratives within the pros and cons discussions of UUCK on YouTube that were built by academics. These four significant narratives are employment issues, regulatory issues, investment, economy and business and environmental issues. The UUCK sentiment was dominated by the rejection of UUCK, as mentioned above. The findings of this study indicate a firm rejection of UUCK, with scientific arguments from academics showing that the government has not built a transparent discussion regarding UUCK. This study recommends a more transparent, open and argumentative discussion from all UUCK stakeholders to minimise community friction.